The Effectiveness of Using Google Sites-based Learning Media on Learning Outcomes in Thermochemistry - Fitri, Dera Ananda; Erlina; Sahputra, Rachmat (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Thermochemistry is one of the most challenging chemistry topics because it requires students to understand abstract concepts while solving mathematical problems. Conventional PowerPoint-based instruction often presents learning materials linearly, providing limited opportunities for students to review concepts independently. This study aimed to examine the effectiveness of Google Sites-based learning media on students’ learning outcomes in thermochemistry. A quasi-experimental study employing a nonrandomized control group pretest–posttest design was conducted with 71 eleventh-grade students at SMAN 8 Pontianak, comprising 36 students in the experimental group and 35 students in the control group. Both groups were taught by the same teacher using the Discovery Learning model over four instructional meetings, with the only difference being the learning media used Google Sites in the experimental group and PowerPoint in the control group. Data were collected using a validated and reliable four-item essay test administered before and after the intervention and were analyzed using Analysis of Covariance (ANCOVA) with pretest scores as the covariate. After controlling for pretest scores, group membership had a significant effect on posttest scores (F(1,68) = 106.794, p < 0.001, partial η² = 0.611). The experimental group also achieved a higher mean posttest score (81.21) than the control group (63.30). These findings suggest that Google Sites-based learning media was associated with higher thermochemistry learning outcomes than conventional PowerPoint-based instruction. The observed effectiveness may be explained by the integration of multimedia representations, structured instructional resources, self-paced study opportunities, and interactive formative feedback that facilitate students’ understanding of abstract thermochemistry concepts.